P15.13.B Role and accuracy of FET-PET in gliomas, and its significance in the differential diagnosis among progression, pseudoprogression, and response to treatments. (5th September 2022) - Caffo, M; La Torre, F; Minutoli, F; Angileri, F F; Caruso, G; Baldari, S; Germanò, A
Abstract: Background: Lack of effective treatments for patients affected by gliomas emphasizes the need for innovative therapeutic approaches. Surgical resection plays a pivotal role in glioma treatment by improving both, progression-free survival (PFS) and overall survival (OS). Gliomas grow beyond contrast enhancement borders, reducing the ability of MRI to determine the tumor burden and predict metabolic change inside tumor. The most appropriate imaging tools to assess early response to treatment is still a matter of debate. In addition, lack of a quantifiable measure of non-enhancing disease progression, mistaking effect of radiation therapy, ischemic injury, or post-operative changes on MRI images can complicate the subject. With O-(2-18Ffluoroethyl)-L-tyrosine ([18F]) FET as a tracer, PET is known to visualize the amino acid uptake in gliomas and thus metabolically active tumor cells, and is a promising methodology providing new data to the currently used RANO criteria. We can distinguish treatment effects (e.g., radiation necrosis and pseudoprogression) as post treatment-related change (PTRC), from findings defined as "true glioma progression" (TPR). Material and Methods: We retrospectively analysed data from 20 patients (15 males and 5 females, mean age 52 years, range 22-75) with diagnosis of glioma (WHO Grade 2: 6, Grade 3: 3, Grade 4:11) who underwent surgery and/or RT and were followed up by MRI and [18F]FET-PET/CT. PET/CT images were acquired by a dual time-point method: an early acquisition at 10 min (600sec acquisition duration) and a late acquisition at 50 min (650 sec acquisition duration) after the administration of 282, 5±47, 8 MBq [18F]FET. Images were visually analyzed. Moreover, a tumor/background ratio (T/B) was obtained by comparing SUV max in the tumoral ROI and SUV max in a mirrored contralateral ROI. Differences between these parameters in patients with recurrence and patients with response to treatments were evaluated by the Mann-Whitney test. Standard of reference was surgery or at least 9 months follow-up. Results: On the basis of our standard of reference, 14 out of 20 patients had tumor recurrence, whereas 6 had PTRC. Visual analysis revealed no abnormal radiotracer accumulation in 4 patients. All these patients had PTRC. As far as semiquantitative analysis is concerned, statistically significant differences were found between tumor recurrence and PTRC for all analyzed indexes. Conclusion: Although magnetic resonance imaging (MRI) is routinely used for serial evaluation of tumor burden in patients with glioma, amino acid positron emission tomography (PET) can be used for confirming the presence of metabolically active tumors. In the follow-up of patient affected by glioma, validation of response to treatments is a need issue, due to the reason that the wrong differentiation between TPR and PTRC could cause a wrong decision made by surgeon and patients.